The occurrence, transformation and control of selenium in coal-fired power plants: Status quo and development. (1st February 2022) - Ma, Shuangchen; Xu, Fang; Qiu, Dao; Fan, Shuaijun; Wang, Ruimin; Li, Yang; Chen, Xiangyang
ABSTRACT: As a trace element, selenium can cause serious harm to organisms when the concentration is too high. Coal-fired power plants are the main source of man-made selenium emissions. How to control the selenium pollution of coal-fired power plants to realize the renewable selenium and the sustainability of coal has not attracted enough attention from the whole world. This paper outlines the conversion and occurrence of selenium in coal-fired power plants. A small part of the selenium produced by combustion can be removed by selective catalytic reduction (SCR) and electrostatic precipitator (ESP) after the gas phase undergoes physical condensation and chemical adsorption to combine with the particulate matter in the flue gas.Because the chemical precipitation method has poor selenium removal effect, the remaining part enters the flue gas desulfurization absorption tower and can be enriched in the desulfurization slurry. The occurrence situation and conversion pathway of selenium in desulfurization slurry are introduced subsequently, the research progress of selenium removal from wet desulfurization wastewater is reviewed from three aspects: physics, biology and chemistry. We believe that the coupling application of oxidation-reduction potential (ORP) and pH can optimize selenium removal in the desulfurization system by improving the oxidation control. As a technology for wet desulfurization system to treat selenium pollution, it has a good development prospect in near future. Implications: Selenium is a trace element present in coal. It is not only of great significance to the life activities of organisms, but also a kind of rare resource. As the most important source of man-made emissions, coal-fired power plants will cause waste of selenium resources and selenium pollution in the surrounding environment. In this study, the occurrence, conversion and control of selenium in coal-fired power plants were systematically sorted out and analyzed. It is helpful for scholars to study the selenium transformation process more deeply. It is of great significance for policy formulation of recommended control technologies and emission limits. It is of great value for the formulation of recommended control technology and the in-depth study of the selenium transformation process.